Wadi’ah dan Hawalah serta Implementasinya dalam Perbankan Syariah - Darmawati, Nia; Zen, Muhamad (CV Kalimasada Group, 2024)
Sharia financial management has different principles from conventional financial management. In managing finances according to sharia principles with Islamic banking institutions, one of the important conditions that must exist is a contract. Among the many contracts that exist, there are wadi'ah and hawalah in contract transactions in Islamic banking. This research aims to analyze the comparison between the concepts of wadi'ah and hawalah in the Islamic banking system. The research involves data collection from various literatures, as well as interviews with Islamic banking experts. The analysis was conducted to understand how these two concepts function in the context of Islamic banking, as well as to identify the differences and similarities between the two. The results show that wadi'ah is a contract that occurs between two parties, where the first party entrusts an item to the second party. The implementation of wadi'ah is in current accounts (liabilities), while hawalah is a contract for the transfer of debt / credit of one party to another. The implementation of hawalah in Islamic banks is in the form of Post Dated Check; it can also be applied to factoring products. This study also highlights the importance of a good understanding of these two concepts, both for customers and Islamic banking institutions, to ensure that the principles of Islamic banking are respected and adhered to.